From Regulatory Gaps to Legal Reform: The Criminalization of Corruption by Private Corporate Officials - Abdul Tono; Faizin Sulistio; Alfons Zakaria (International Journal of Law, Crime and Justice, 2026)
This study examines the urgency of criminalizing corruption in the private corporate sector within the Indonesian legal system. Despite Indonesia’s ratification of the United Nations Convention Against Corruption (UNCAC) through Law Number 7 of 2006, the current anti-corruption legal framework remains primarily focused on state losses, leaving a regulatory gap in addressing inter-private corruption. This research employs a normative legal approach to analyze the implications of this legal vacuum on market integrity, corporate governance, and economic development. The findings indicate that the absence of comprehensive regulation on private sector corruption weakens law enforcement, facilitates anti-competitive practices such as cartels and bid rigging, and undermines investor confidence. Furthermore, it disrupts fair business competition, harms shareholders’ interests, and contributes to inefficiencies in resource allocation. The study argues that criminalizing corruption in the private sector is essential not only to fulfill international obligations under UNCAC but also to promote healthy competition, protect public and corporate interests, and support sustainable economic growth. It recommends the formulation of specific criminal provisions addressing private sector corruption, strengthening corporate accountability mechanisms, and integrating enforcement across legal sectors to ensure effective prevention and deterrence.